PEMBINAAN AGAMA ISLAM DI PESANTREN MUNTASIRUL ULUM MAN YOGYAKARTA III (Tinjauan Psikologi Humanistik-Religius) - Hamruni Hamruni (Jurnal Pendidikan Agama Islam, 2016)
Muntasyirul Ulum Boarding School is dormitory for students MAN Yogyakarta III. Coachingmaterials integrated with lessons in Yogyakarta MAN III, including deepening the material in theform of religion and religious formation of creative and independent character. Serious coaching fromBoarding School is done by providing guidance, either individually or in groups. Individual coachingaimed at guiding students through a turbulent adolescence. Guidance also be directed so that studentscan carry out their duties as students, have an independent person and is able to actualize the potentialand talent to be individual resilient in the face of adversity. In addition, the guidance also seeks to equipand nurture students to become strong personal faith. By using a method that is inspiring dialogue, theboarding seeks to educate and equips them with the nature of humanity, tolerance and pluralism. Thisis in line with the concept of religion in fostering humanistic attempt that students are not only able todo the actualization of the material, but also embodies adherence to the revelation.Keywords: Humanism, actualization,tolerance.